Optimization of porphyrin dyes with a bulky triphenylamine donor for developing efficient dye-sensitized solar cells. (March 2021) - Tang, Yunyu; Wang, Yueqiang; Yan, Qifan; Zeng, Kaiwen; Tang, Weiqiang; Zhao, Shuangliang; Kong, Cong; Xie, Yongshu
Abstract: To fabricate efficient dye-sensitized solar cells (DSSCs), three porphyrin dyes XW65 −XW67 have been designed and synthesized using a bulky triphenylamine donor. Based on our previously reported dyes with a carbazole donor, a bulky triphenylamine unit was employed as the donor to synthesize XW65 with the aim to enhance the electron donating ability and suppress dye aggregation. As a result, XW65 shows enhanced photocurrent density ( J sc ) and open circuit voltage ( V oc ), affording a high efficiency of 9.02%. On this basis, XW66 was synthesized with a methyl group introduced into the carboxyphenyl acceptor to further suppress dye aggregation and improve the V oc, achieving an enhanced efficiency of 9.23% with improved V oc of 849 mV and J sc of 14.87 mA cm −2, which can be ascribed to the further suppressed dye aggregation and enhanced adsorption amount on the TiO2 film induced by the additional methyl group. To further improve the J sc, a benzothiadiazole (BTD) unit has been introduced as the auxiliary acceptor to afford XW67, which exhibits a strikingly red-shifted monochromatic photon-to-electron conversion efficiency (IPCE) onset wavelength of 830 nm, obtaining the highest J sc value of 15.83 mA cm −2 among the three dyes. Consequently, despite the sacrifice of V oc caused by the severe dye aggregation associated the extended conjugation framework, XW67 exhibits the highest efficiency of 9.43%. On this basis, cosensitization with WS-5 afforded elevated efficiencies of 10.07%, 10.38% and 10.13% for XW65 −XW67, respectively, owing to the simultaneously enhanced J sc and V oc . These results indicate that it is effective to develop efficient DSSCs based on cosensitization of optimized porphyrin dyes containing a bulky triphenylamine donor, a methyl group on the carboxyphenyl acceptor, and an auxiliary electron acceptor. Graphical abstract: Image 1 Highlights: A strikingly red-shifted monochromatic incident photon to current conversion efficiency (IPCE) onset wavelength of 830 nm. Better suppression of dye-aggregation and by bulky substituents on the donor and a methyl group on the carboxyphenyl acceptor. The absorption drawbacks of the porphyrin dyes compensated by a broad band of the cosensitizer. An efficiency 10.38% achieved with synergetically enhanced V oc and J sc .